FLUIDOT: A Modular Microfluidic Platform for Single‐Cell Study and Retrieval, with Applications in Drug Tolerance Screening and Antibody Mining (Small Methods 3/2023). Issue 3 (13th March 2023) - Breukers, Jolien; Ven, Karen; Struyfs, Caroline; Ampofo, Louanne; Rutten, Iene; Imbrechts, Maya; Pollet, Francesca; Van Lent, Julie; Kerstens, Winnie; Noppen, Sam; Schols, Dominique; De Munter, Paul; et al.
Abstract : Front Cover In article number 2201477, Lammertyn and co‐workers developed FLUIDOT, a modular microfluidic platform in which microwells, optical tweezers, and an interchangeable cell‐retrieval system are combined to enable in‐depth screening and specific retrieval of single cells. They demonstrated the versatility of FLUIDOT by implementing applications in drug tolerance screening and antibody mining. The cover was designed by Jorik Waeterschoot.